The Protein Biochemistry of the Postsynaptic Density in Glutamatergic Synapses Mediates Learning in Neural Networks - Kennedy, Mary B. (Biochemistry, 2018)
The strength of each excitatory synapse in the central nervous system is regulated by its prior activity in a process called synaptic plasticity. The initiation of synaptic plasticity occurs when calcium ions enter the postsynaptic compartment and encounter a subcellular structure called the postsynaptic density (PSD). The PSD is attached to the postsynaptic membrane just underneath the concentrated plaque of neurotransmitter receptors. It is comprised of a core set of 30–60 proteins, approximately 20 of which are scaffold proteins. The rest include protein kinases and phosphatases, some of which respond to calcium ion; small GTPases and their regulators; chaperones; ubiquitins; and proteases. The assembly of the PSD involves competitive binding among a variety of specific protein binding sites to form a dynamic network. A biochemical challenge for the future is to understand how the dynamic regulation of the structure, composition, and activity of the PSD mediates synaptic plasticity and how mutations in PSD proteins lead to mental and neurodegenerative diseases.